Synthesis and Characterization of Ni(II) Complex of S3N2H2 - KUMAR, MANOJ; JADON, S.P.S. (Asian Journal of Chemistry, 2010)
On the basis of quantitative estimations, mass IR, UV and 1H NMR spectra, the complex of S3N2H2 with Ni(II) compound, has been assigned as (S3N2H2)2·NiSO4·6H2O, having quardidentated co-ordinated, Ni2+ ion bridged sandwich geometrical structure.